Research methodologies in engineering sciences: a critical analysis - Ariza Flores, Víctor André (2023)
This study evaluates the research methodologies utilized in the engineering sciences. The primary goal is to identify best practices in research design, data acquisition, and result interpretation to suggestfuture engineering research. A systematic literature review evaluatedthe methodological approaches and trends of studies published over the past decade. Thestudy's methodology included article selection based on predefined criteria,data extraction on research design, data collection and analysis methods, andresult communication. The results revealed a variety of approaches and techniques, with quantitativeresearch predominating, although an increase in the use of qualitative and blended methods was also noted. There were identified trends in research design, data acquisition and analysis, and communication of results that reflect the evolution and requirements of the engineering field. This study concludes by emphasizing the significance of understanding and employing various approaches and techniques in engineering researchto address the field's complex and interdisciplinary problems effectively. By promoting methodological diversity and adopting best practices in research design, data collection and analysis, and result communication, engineering researchers and professionals can improve the quality and impact of their research and make significant contributions to advancingengineering knowledge and problem-solving.